Development and Characterization of Somatic Hybrids of Ulva reticulata Forsskål (×) Monostroma oxyspermum (Kutz.)Doty - Gupta, Vishal; Kumari, Puja; Reddy, CRK (Frontiers in Plant Science, 2015)
Ulvophycean species with diverse trait characteristics provide an opportunity to create novel allelic recombinant variants. The present study reports the development of seaweed variants with improved agronomic traits through protoplast fusion between Monostroma oxyspermum (Kutz.) Doty and Ulva reticulata Forsskål. A total of 12 putative hybrids were screened based on the variations in morphology and total DNA content over the fusion partners. DNA-fingerprinting by inter simple sequence repeat (ISSR) and amplified fragment length polymorphism (AFLP) analysis confirmed genomic introgression in the hybrids. The DNA fingerprint revealed sharing of parental alleles in regenerated hybrids and a few alleles that were unique to hybrids. The epigenetic variations in hybrids estimated in terms of DNA methylation polymorphism also revealed sharing of methylation loci with both the fusion partners. The functional trait analysis for growth showed a hybrid with heterotic trait (DGR% = 36.7 ± 1.55%) over the fusion partners U. reticulata (33.2 ± 2.6%) and M. oxyspermum (17.8 ± 1.77%), while others were superior to the mid-parental value (25.2 ± 2.2%) (p < 0.05). The fatty acid (FA) analysis of hybrids showed notable variations over fusion partners. Most hybrids showed increased polyunsaturated FAs (PUFAs) compared to saturated FAs (SFAs) and mainly includes the nutritionally important linoleic acid, α-linolenic acid, oleic acid, stearidonic acid, and docosahexaenoic acid. The other differences observed include superior cellulose content and antioxidative potential in hybrids over fusion partners. The hybrid varieties with superior traits developed in this study unequivocally demonstrate the significance of protoplast fusion technique in developing improved varients of macroalgae.